Where are markets? - Peck, Jamie (Market/Place: Exploring Spaces of Exchange, 2020)
The goal of this chapter is to prepare the ground for theorizing the diversity and spatiality of markets, (necessarily) dealing with, but seeking to move concertedly beyond, the restrictive optic of the orthodox model. It seeks to do so by way of three steps. The following section opens up some preliminary questions about the place of markets and their actually existing historical geography. Next, the chapter turns to the challenge of decentring the market, of moving beyond the idea that the market properly and eternally belongs at the centre of the economic universe. What is the scope for understanding “real markets”, both conceptually and empirically, without recourse to the idealized model of the “pure” market, and all its downstream distortions? Finally, the chapter addresses the question of alternative “mappings” of markets, taking some cues from the work of Karl Polanyi, but urging a more thoroughgoing reconstruction. The chapter’s conclusion acknowledges that the “where?” of markets remains a demanding theoretical question, such that what follows serves to inform some different points of departure, not the destination itself. New answers to this “where?” question, though properly a matter for what Polanyi characterizes as the “substantivist” investigation of real-world market formation, re-formation and transformation, ought to recognize, inter alia: first, the relational character of markets, which are codependent on non-market modes of coordination and regulation; second, their “instituted” form, necessary in function but variable in practice; and not least, third, their always out-of-equilibrium processual dynamics and contradictions.
Geography
Keywords: markets; space

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Geography; Interdisciplanary studies
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets